2023
DOI: 10.3390/cells12081177
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis Implicates CASK-Liprin-α2 Interaction in Cerebellar Granular Cell Death in MICPCH Syndrome

Abstract: Microcephaly with pontine and cerebellar hypoplasia (MICPCH) syndrome is a neurodevelopmental disorder caused by the deficiency of the X-chromosomal gene CASK. However, the molecular mechanisms by which CASK deficiency causes cerebellar hypoplasia in this syndrome remain elusive. In this study, we used CASK knockout (KO) mice as models for MICPCH syndrome and investigated the effect of CASK mutants. Female CASK heterozygote KO mice replicate the progressive cerebellar hypoplasia observed in MICPCH syndrome. CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…MICPCH/microcephaly is one of the phenotypes of CASK -related disorders that has been extensively examined in animal models. The cerebellar size of cask heterozygous knockout female mice and hypomorphic male mice was shown to be smaller than that in wild-type mice [ 4 , 92 , 94 , 95 ]. Similarly, we reported that the knockout of neurexin, a main binding partner of CASK, from the cerebellar granule cells, induced cell death.…”
Section: Phenotypes and Functional Domains Of Caskmentioning
confidence: 99%
See 4 more Smart Citations
“…MICPCH/microcephaly is one of the phenotypes of CASK -related disorders that has been extensively examined in animal models. The cerebellar size of cask heterozygous knockout female mice and hypomorphic male mice was shown to be smaller than that in wild-type mice [ 4 , 92 , 94 , 95 ]. Similarly, we reported that the knockout of neurexin, a main binding partner of CASK, from the cerebellar granule cells, induced cell death.…”
Section: Phenotypes and Functional Domains Of Caskmentioning
confidence: 99%
“…The importance of the PDZ domain in cerebellar development is supported not only by genetic findings of missense mutations in the PDZ domain but also by our recent report using cerebellar granule cell culture. We demonstrated that the death of cerebellar granule cells from the conditional knockout of CASK can be rescued by the full length of CASK but not by the variants lacking the CaMK, PDZ, or SH3 domains of CASK, indicating that all three domains are essential for the survival of cerebellar granule cells in mice [ 95 ]. Moreover, one of the MICPCH-associated missense mutations (M519T), which could not bind to neurexin in vitro assay [ 63 ], failed to rescue the cell death of cerebellar granule cells from the knockout of the cask gene [ 95 ], indicating that CASK–neurexin binding would be important to cerebellar development.…”
Section: Phenotypes and Functional Domains Of Caskmentioning
confidence: 99%
See 3 more Smart Citations